KOMUNIKASI PERSUASIF DINAS KESEHATAN KOTA PEKANBARU DALAM UPAYA PENCEGAHAN DEMAM BERDARAH DENGUE (DBD) - Shalad Mulianazar; Nurjanah " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Dengue fever is a disease that is endemic in society, especially when it's the rainy season. The problem of dengue fever in the city of Pekanbaru, can not be prevented only by an appeal of the government alone, but to the awareness of the public of Pekanbaru will be the prevention of dengue fever. Pekanbaru City Health Department take steps to prevent dengue by means mempersuasif people to understand what actions should be taken to prevent dengue fever. This study aims to find a persuasive approach, messages and media used by the City Health Office Pekanbaru. In dengue prevention efforts for people in the city of Pekanbaru.This study uses descriptive qualitative research. Informants consisted of eight people who is the Head, Employee Health Office Pekanbaru, people who are victims in an area where there are many victims of dengue fever in the city of Pekanbaru by using purposive sampling technique. Data collected by observation, interview and documentation. To achieve the validity of the data in this study, researchers used an extension extension of participation.The results showed that the City Health Office Pekanbaru use a persuasive approach to using the media to convey the prevention of dengue fever, the nature of the persuader targeted with indirect communication to the public but is expected to be delivered the message in the prevention of dengue fever, and the approach of psychosocial form approach bulk order can be persuasive on the whole community in the city of Pekanbaru. Persuasive message Pekanbaru City Health Department is using verbal messages include clarity, candor, and the precision and nonverbal messages in the form of an implied message through state of the number of victims, the statistical increase in the number of victims and the environment around the residence. Pekanbaru City Health Department to use the mass media for the first mempersuasif with print and online media, with newspapers and websites such as newspaper stands, riaupos and website stands between nasional.Dan pekanbaru and also through the use of electronic media such as radio and television fress, RRI, Persada as well as talk shows and the fm fress RTV.Keywords : Communication persuasive, dengue fever, Pekanbaru City Health Department, public